Associação entre sobrepeso/obesidade e desfechos odontológicos em escolares de Porto Alegre, RS - Lock, Nicássia Cioquetta (2018)
The present dissertation is composed of two manuscripts whose objectives are to analyze the association between overweight/obesity and changes in dental caries index (Article I) and to study the association between overweight/obesity and the prevalence of gingivitis (Article II) among schoolchildren from Porto Alegre, RS. The study is linked to an epidemiological survey conducted to assess the oral health conditions of schoolchildren from Porto Alegre, RS. At baseline, between 2009 and 2010, 1,528 schoolchildren were examined. After a mean follow-up period of 2.5 years, between 2012 and 2013, a longitudinal component was incorporated to the cross-sectional study and 801 students were reexamined. Data collection included the application of questionnaires, the recording of anthropometric measures (height and weight) and clinical examination, according to the following systematics: recording of the gingival bleeding index, professional cleaning, drying and recording of the dental caries index (non-cavitated and cavitated, inactive and active lesions). The primary outcome of Article I was ΔDMFS index, defined as the difference between the final and the basal DMFS. The primary outcome of Article II was prevalence of gingivitis, defined on the basis of the mean/median (52% of bleeding sites). Based on height and weight data, the BMI(body mass index)-for-age Z-score was calculated and the students were classified as normal, overweight, or obese according to cut-off points proposed by the World Health Organization. In both manuscripts, weight status was considered the main predictor variable. Preliminary analyses were performed to compare the outcomes according to categories of predictor variables using the Wald test. The association between predictor variables and ΔDMFS and prevalence of gingivitis was evaluated using negative binomial and Poisson regression models, respectively (unadjusted and adjusted). An adjusted polynomial model was designed to explore the association between BMI-for-age Z-score and ΔDMFS. In Article I, obese schoolchildren presented significantly lower ΔDMFS than did normal weight subjects (0.42 versus 0.86, p <0.05). In the risk assessment analysis, we found a numerical tendency of lower risk of ΔDMFS among obese individuals compared to normal weight ones, but statistical significance was not reached. The polynomial model showed a significant nonlinear relationship (inverted U shape) between the BMI-for-age Z-score and ΔDMFS. In Article II, it was observed that obese girls were at higher risk of having gingivitis (Adjusted Prevalence Ratio = 1.20, 95% CI = 1.09-1.31, p <0.001). This association was not observed among boys. This study concluded that (I) obese adolescents had lower ΔDMFS over a period of 2.5 years, and (II) obese girls had a higher risk of presenting gingivitis.